A Carbene‐Stabilized Boryl‐Phosphinidene. Issue 31 (13th April 2022) - Kumar Sarkar, Samir; Kundu, Subrata; Nazish, Mohd; Kretsch, Johannes; Herbst‐Irmer, Regine; Stalke, Dietmar; Parvathy, Parameswaran; Parameswaran, Pattiyil; Roesky, Herbert W.
Abstract: Herein, the synthesis and characterization of the carbene‐stabilized boryl phosphinidenes 1 –3 are reported. Compounds 1 –3 are obtained by reacting Me‐cAAC=PK (Me2 ‐cAAC=dimethyl cyclic(alkyl)(amino)carbene) and dihaloaryl borane in toluene. All three compounds were characterized by X‐ray crystallography. Quantum mechanical studies indicated that these compounds have two lone pairs on the P center viz., an σ‐type lone pair and a "hidden" π‐type lone pair. Hence, these compounds can act as double Lewis bases, and the basicity of the π‐type lone pair is higher than the σ‐type lone pair. Abstract : What hides within : Three different singlet boryl phosphinidenes were synthesized by using cAAC carbene, and their inversely polarized phosphaalkene characteristics were investigated. Quantum mechanical studies suggest that the P center of these boryl phosphinidenes contains two lone pairs viz., an σ‐type lone pair and a "hidden" π‐type lone pair.